Search for heavy resonances decaying to Zðνν¯ÞVðqq¯0 Þ in proton-proton collisions at ffiffi s p = 13 TeV - CMS Collaboration; Damarseçkin, Serdal (American Physical Society, 2022)
A search is presented for heavy bosons decaying to Z(νν¯)V(qq¯′), where V can be a W or a Z boson. A sample of proton-proton collision data at s=13 TeV was collected by the CMS experiment during 2016-2018. The data correspond to an integrated luminosity of 137 fb-1. The event categorization is based on the presence of high-momentum jets in the forward region to identify production through weak vector boson fusion. Additional categorization uses jet substructure techniques and the presence of large missing transverse momentum to identify W and Z bosons decaying to quarks and neutrinos, respectively. The dominant standard model backgrounds are estimated using data taken from control regions. The results are interpreted in terms of radion, W′ boson, and graviton models, under the assumption that these bosons are produced via gluon-gluon fusion, Drell-Yan, or weak vector boson fusion processes. No evidence is found for physics beyond the standard model. Upper limits are set at 95% confidence level on various types of hypothetical new bosons. Observed (expected) exclusion limits on the masses of these bosons range from 1.2 to 4.0 (1.1 to 3.7) TeV.